2008
DOI: 10.1128/aem.02496-07
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Conditions Promote Expression of Sfp Fimbriae and Adherence of Sorbitol-Fermenting Enterohemorrhagic Escherichia coli O157:NM to Human Intestinal Epithelial Cells

Abstract: The sfp gene cluster, unique to sorbitol-fermenting (SF) enterohemorrhagic Escherichia coli (EHEC) O157:NM strains, encodes fimbriae that mediate mannose-resistant hemagglutination in laboratory E. coli strains but are not expressed in wild-type SF EHEC O157:NM strains under standard laboratory conditions. We investigated whether Sfp fimbriae are expressed under conditions that mimic the intestinal environment and whether they contribute to the adherence of SF EHEC O157:NM strains to human intestinal epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 52 publications
1
41
0
5
Order By: Relevance
“…In addition, SF E. coli O157:NM strains have been shown to possess a unique fimbrial cluster encoded on their large plasmid, pSFO157, which mediates the expression of Sfp fimbriae (9). Recently published work demonstrates that Sfp fimbriae are expressed by SF STEC O157:NM strains cultured under anaerobic conditions on solid media simulating the colonic environment and that the induction of Sfp fimbriae on wild-type SF STEC O157:NM strains correlated with increased adherence to Caco-2 and HCT-8 cells (38). Single asterisks indicate that, following culture on CFA agar, the CR-positive SF STEC O157:NM strain E02/879 adhered to Caco-2 cells at significantly higher levels than the CR-negative SF STEC O157:NM strains 340/97 and 080/01 (P Ͻ 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SF E. coli O157:NM strains have been shown to possess a unique fimbrial cluster encoded on their large plasmid, pSFO157, which mediates the expression of Sfp fimbriae (9). Recently published work demonstrates that Sfp fimbriae are expressed by SF STEC O157:NM strains cultured under anaerobic conditions on solid media simulating the colonic environment and that the induction of Sfp fimbriae on wild-type SF STEC O157:NM strains correlated with increased adherence to Caco-2 and HCT-8 cells (38). Single asterisks indicate that, following culture on CFA agar, the CR-positive SF STEC O157:NM strain E02/879 adhered to Caco-2 cells at significantly higher levels than the CR-negative SF STEC O157:NM strains 340/97 and 080/01 (P Ͻ 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In SFO157:NM, the sfp operon is found on the pSFO157 virulence plasmid and was found to be involved in autoagglutination (311). Expression of the sfp under laboratory conditions required anaerobic conditions (312). Although sfp is gen- erally thought to be restricted to SFO157:NM isolates, it has been found in STEC O165:H25/NM (313).…”
Section: Pathogenesismentioning
confidence: 99%
“…The plasmids of STEC are highly variable genetic elements (14), and surveys of STEC strains of various serogroups and other DECs revealed the sfpA and sfpDG regions to be restricted to SF STEC O157:H Ϫ (13, 30). The contribution of Sfp fimbriae to the adherence of SF STEC O157:NM strains to human intestinal epithelial cells has been investigated, and the data showed that the expression of Sfp fimbriae is induced under anaerobic conditions (resembling those of the natural site of infection) and that induction of Sfp fimbriae correlates with increased adherence to Caco-2 and HCT-8 cells (58).…”
Section: Other Stec Fimbriae: Sfp Fimbriaementioning
confidence: 99%